The n-terminal extension of the mycobacterium avium rel protein is a dual regulator of the bifunctional enzyme and represents a novel target - Tuck Choy Fong; Priya Ragunathan; Reema Alag; Carlos Silvester; Svarika Sonthalia; Vikneswaran Mathiyazakan; Vandana Grover; Gerhard Grüber (MDPI, 2025)
Mycobacterium avium (Mav) is a leading cause of pulmonary disease among non-tuberculous mycobacteria (NTMs) due to its extensive antibiotic resistance profile. The essential Rel protein is a bifunctional enzyme, which is sensitive to environmental stress and regulates cellular guanosine-3′,5′-bispyrophosphate ((p)ppGpp). Increased levels of the alarm one thereby initiates a survival response, contributing to bacterial persistence and virulence. Objectives: MavRel harbors an unusual extension at the N-terminal domain (NTD), which we aim to characterize its possible regulatory role in maintaining (p)ppGpp homeostasis. We also studied whether the TGS domain retains its regulation capacity in MavRel and the binding propensity of the ACT domain to valine. Methods: Molecular dissection of MavRel was performed to generate a series of truncates to quantify the synthetase and hydrolase activities. Binding experiments with tRNA and valine were carried out via tryptophan quenching assay and NMR, respectively. Results: Biocatalytic regulation of MavRel was found to be predominantly governed by the residues 37– 50 at the NTD extension in its free state. The TGS domain was shown to harbor the capacity to bind with deacylated tRNA and represses synthetase activity to a lower degree compared to the NTD extension. We also characterized the dimeric Mav ACT-domain and the interacting residues contributing to its affinity with valine to function as a nutrient sensor. Conclusions: The mapping of the unique NTD regulatory element of MavRel reveals its functional relevance to coordinate the catalytic states of synthetase and hydrolase, hence underscores the prospect to drive inhibitor development targeting this novel site against Mav infections.